Estimation of thermal conduction in hollow-glass-beads-filled cement-based composites by variational asymptotic homogenization method. (October 2019) - Xiao, Peng; Yifeng, Zhong; Peng, Wang; Dan, Luo
Highlights: A heat conduction micro-model of HGB-CBCs is established based on VAHM. The influence of two different types of unit cells on the effective thermal conductivity is investigated. The sudden changes of local heat flux around the interface between HGB and matrix are well captured by VAHM. HGB-CBCs with greater volume fraction and smaller wall thickness of HGB provides better thermal insulation effect. Complex conduction paths around the bead wall are beneficial to the decrease of effective thermal conductivity. Abstract: As a lightweight building material, hollow-glass-beads-filled cement-based composites (HGB-CBCs) have important applications in building energy saving and fireproofing. In order to reveal the mechanism of thermal conduction in HGB-CBCs, a heat conduction micro-model of HGB-CBCs was established based on the variational asymptotic homogenization method (VAHM). Then, the heat conduction micro-model was used to quantitatively investigate the influence of the micro-structural parameters and constituent properties on the effective thermal conductivity of HGB-CBCs with two different types of unit cells. Numerical results show that the heat flux fields recovered by VAHM perfectly agree with those by RVE-based FEM, but more smooth. The heat flux will drop slowly and almost linearly far away from the glass bead, while the heat flux in HGB will drop sharply, indicating HGB has great thermal resistance. HGB-CBCs with greater volume fraction and smaller wall thickness of HGB provides better thermal insulation effect. The longer and more complicated heat transfer paths around the wall of HGB are beneficial to the decrease of effective thermal conductivity, which can provide guidance for engineers who want to use HGB-CBCs as thermal-insulating composite materials in the civil engineering.